Quasi‐Resonant Tunneling Transport in Magnetic CrBr3 - Gen Long; Peiheng Jiang; Zishu Zhou; Meizhen Huang; Binglan Wu; Zhicheng Zhong; Sunan Ding; Ning Wang; Guangyu Zhang (Advanced Physics Research)
Abstract Tunneling techniques are pivotal for probing 2D magnetic materials. While the Fowler‐Nordheim model describes tunneling in bulk materials through bias‐induced triangular potentials, van der Waals layered systems require special consideration of interlayer gaps. The fundamental mechanisms of tunneling processes in van der Waals magnetic materials are delved into, with a specific emphasis on CrBr3. Layer‐resolved quasi‐resonant tunneling (QRT) mediated by ladder‐shaped barriers is revealed. QRT occurs because the outermost CrBr3 conduction band aligns with the Fermi level of the tunneling electrode under the bias voltage tilting, resulting in an increased tunneling probability and enhanced current. Two competing mechanisms driven by the magnetic field—the suppression of spin fluctuations leading to negative tunneling magnetoresistance (TMR) and the spin‐flip‐induced elevation of the conduction band energy causing positive TMR—are identified to explain the diverse behaviors of tunneling magnetoresistance under different bias voltages and temperatures. The work establishes van der Waals heterostructures as distinct tunneling systems differing fundamentally from conventional bulk barriers, while introducing the QRT concept as a critical advancement in understanding electronic tunneling in layered materials.